Stories of Hell and Healing: Internet Users' Construction of Benzodiazepine Distress and Withdrawal. (November 2017) - Fixsen, Alison M.; Ridge, Damien
Benzodiazepines are a group of drugs used mainly as sedatives, hypnotics, antiepileptics, and muscle relaxants. Consumption is recommended for 2 to 4 weeks only, due to fast onset of dependency and potentially distressing withdrawal symptoms. Few peer-review studies have drawn on the user experiences and language to appreciate firsthand experiences of benzodiazepine withdrawal or discontinuation syndrome. We looked extensively at patient stories of benzodiazepine withdrawal and recovery on Internet support sites and YouTube. Our analysis indicated that users employ rich metaphors to portray the psychologically disturbing and protracted nature of their suffering. We identified seven major themes: hell and isolation, anxiety and depression, alienation, physical distress, anger and remorse, waves and windows, and healing and renewal. By posting success stories, ex-users make known that "healing" can be a long, unpredictable process, but distress does lessen, and recovery can happen.